Crohn's disease and hyperbaric oxygen therapy - Iezzi,Leonardo Estenio (2011)
PURPOSE: Evaluate the application of Hyperbaric Oxygen Therapy (HBO) in patients with Crohn's disease (CD) refractory to pharmacologic therapy, who developed abdominal, anorectal or skin complications. METHODS: Fourteen selected patients with refractory CD and treated at the School of Medicine of Ribeirao Preto, University of Sao Paulo (FMRP-USP) and at the Center of Hyperbaric Medicine, São Paulo Hospital (CEMEHI) were submitted to HBO. RESULTS: Of the 14 patients evaluated, 11 had a satisfactory response. CONCLUSION: HBO has shown benefits in patients with CD refractory to pharmacologic therapy.